2019
DOI: 10.25247/2447-861x.2019.n246.p54-68
|View full text |Cite
|
Sign up to set email alerts
|

O Cuidador Em Serviço Residencial Terapêutico (Srt) No Município De Salvador-Ba

Abstract: <p>O Serviço Residencial Terapêutico é um instrumento imprescindível de direitos humanos no processo de desinstitucionalização psiquiátrica e retorno do individuo com transtorno mental ao meio social, para existir como ser de direitos e deveres. A casa se torna o núcleo das relações interpessoais e o ponto de partida ao início de vidas que foram tombadas por um modelo hegemônico e opressor. Um indivíduo em sofrimento psíquico não pode ter a sua vida pré-estabelecida por conta do preconceito e intolerânci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
3
0
2
Order By: Relevance
“…Characterization of the studies The countries that made up the 10 articles selected for data extraction regarding the work of caregivers in this research were: 60% national (Brazil) [19][20][21][22][23][24] and 40% international (Ireland, Italy, China and Belgium). [25][26][27][28] Regarding the years of publication, the two oldest articles, 2004 28 and 2008, 27 refer to international productions, respectively Belgium28 and China.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Characterization of the studies The countries that made up the 10 articles selected for data extraction regarding the work of caregivers in this research were: 60% national (Brazil) [19][20][21][22][23][24] and 40% international (Ireland, Italy, China and Belgium). [25][26][27][28] Regarding the years of publication, the two oldest articles, 2004 28 and 2008, 27 refer to international productions, respectively Belgium28 and China.…”
Section: Resultsmentioning
confidence: 99%
“…The predominance of national articles starts from 2011, with two articles from this year, [23][24] one from 2018 20 and two from 2019. 19,22 Regarding the method, 60% used mixed methods with predominance of semi-structured interviews, associated with direct and systematic observation, field diaries, intervention and control groups, postal questionnaires, among others; [21][22][23][24][25][26][27] 40% used a single method, with semi-structured interview, questionnaire and application of tests. [19][20]26,28 Regarding the objective of the studies, it is identified that in the national articles the interest in knowing, analyzing and bringing reflections on the work of caregivers in relation to their weaknesses, potentialities, realities and difficulties predominates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ainda nesta perspectiva, faz-se necessário, o aprimoramento das técnicas do cuidar, assim como a melhoria nas condições de trabalho e infraestrutura no geral (Sande & Christovam, 2019).…”
Section: Corpus Final (N=15)unclassified
“…Dessa forma destaca-se a importância de mais estudos sobre a temática e também de estudos que priorizem a colaboração de outros setores da sociedade, e a construção de uma rede solidária que torna o cuidado uma tarefa mais assertiva e equilibrada, que garanta melhor assistência e diminua as sobrecargas emocionais, físicas e sociais desses trablhadores. (Palombini et al, 2010;Sande & Christovam, 2019).…”
Section: Corpus Final (N=15)unclassified